GAMBARAN TEKANAN DARAH SISTOLIK PADA KEJADIAN MORTALTAS PASIEN STEMI DI RSUD ULIN BANJARMASIN - Ramadhani, Khairir; Wahid, Abdurahman; Hafifah, Ifa (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Blood pressure having an important role in determining risk stratification and prognosticinformation that is effective, in which low blood pressure is associated with a high incidence ofmortality. The objective in this study is describing systolic number of blood pressure and inHospital Mortality of STEMI patients in RSUD Ulin Banjarmasin. This study used univariateanalysis. The method used was a descriptive study with cross sectional sample types accidental.Performed in STEMI patients in hospitals Ulin Banjarmasin and involves 17 patients researchconducted from November 4th to December 6th 2015. Of the total respondents were 17 people, 15of respondents (88,2%) categorized survive with systolic blood pressure an average of 116.67mmHg, 2 respondents (11,8%) categorized mortal with systolic blood pressure an average of 80mmHg. STEMI Patients with systolic blood pressure of 80 mmHg had a higher incidence ofmortality than patients with systolic blood pressure greater than 80 mmHg.